PKCγ participates in food entrainment by regulating BMAL1 - Zhang, Luoying (National Academy of Sciences, 2012)
Temporally restricted feeding (RF) can phase reset the circadian clocks in numerous tissues in mammals, contributing to altered timing of behavioral and physiological rhythms. However, little is known regarding the underlying molecular mechanism. Here we demonstrate a role for the gamma isotype of protein kinase C (PKCγ) in food-mediated entrainment of behavior and the molecular clock. We found that daytime RF reduced late-night activity in wild-type mice but not mice homozygous for a null mutation of PKCγ (PKCγ(−/−)). Molecular analysis revealed that PKCγ exhibited RF-induced changes in activation patterns in the cerebral cortex and that RF failed to substantially phase shift the oscillation of clock gene transcripts in the absence of PKCγ. PKCγ exerts effects on the clock, at least in part, by stabilizing the core clock component brain and muscle aryl hydrocarbon receptor nuclear translocator like 1 (BMAL1) and reducing its ubiquitylation in a deubiquitination-dependent manner. Taken together, these results suggest that PKCγ plays a role in food entrainment by regulating BMAL1 stability.